Profile of Student Academic Procrastination Behavior in Problem Solving and Mathematical Digital Literacy - Aidha Rosalia Agustin; Widodo Winarso (Didaktik Matematika, 2021)
The phenomenon of procrastination behavior in problem-solving and mathematical digital literacy still occurs among students. This study aimed to analyze the profile of students' academic procrastination behavior in problem-solving and mathematical digital literacy-purposive sampling technique involving 19 students of one junior high school in Indonesia. Academic procrastination behavior is obtained through qualitative research with a case study approach using the Tuckman Procrastination Scale (TPS) instrument, digital literacy scale, mathematical problem-solving ability tests, and semi-structured interviews as well as data analysis with four steps of research, namely data collection, data reduction, data presentation, and concluding. Most of the students (84.2%) experienced academic procrastination in solving mathematical problems and mathematical digital literacy (21%). There are six kinds of problem-solving and mathematical digital literacy student profiles in the high, moderate, and low category.